How Do Mean Division Shares Affect Growth and Development? - Shao, Liang Frank (Panoeconomicus, 2017)
The Gini coefficient is widely used in academia to discuss how income inequality affects development and growth. However, different Lorenz curves may provide different development and growth outcomes while still leading to the same Gini coefficient. This paper studies the development ef- fects of “mean division shares”, i.e., the share of income (mean income share) held by people whose household disposable income per capita is below the mean income and the share of the population (mean population share) with this income, using panel data. Our analysis explores how this income share and population share impact development and growth. It shows that the income and population shares affect growth in significantly different ways and that an analysis of these metrics provides substantial value compared to that of the Gini coefficient.Key words: Income inequality, Mean division shares, Growth.JEL: C36, D31, O11.Gini koeficijent se često koristi u nauci kako bi se razmotrio način na koji dohodna nejednakost utiče na razvoj i rast. Međutim, različite Lorenzove krive mogu dati različite ishode razvoja i rasta iako vode ka istom Gini koeficijentu. U radu se proučava efekte razvoja “prosečne podele dohodnog učešća”, tj. učešće prihoda (prosečnog dohodka) od strane ljudi čije domaćinstvo raspolaže sa raspoloživim dohotkom po glavi stanovnika koji je ispod prosečnog prihoda, kao i udeo stanovništva (prosečni udeo stanovništva) koji ima ovakav prihod, koristeći panel podatke. Naša analiza istražuje kako ovaj udeo prihoda i udeo stanovništva utiče na razvoj i rast. Rezultati pokazuju da dohodak i udeo stanovništva utiču na rast na značajno različite načine i da analiza ovih pokazatelja pruža značajnu vrednost u poređenju sa Gini koeficijentom.Ključne reči: Dohodovna nejednakost, Prosečan udeo divizija, Rast.